Preliminary report on MFM measurements on magnetic nanofiber mats - Raphael Weiss; Andrea Ehrmann (Communications in Development and Assembling of Textile Products)
Nanofiber mats can be produced unambiguously by electrospinning. Besides pure polymers or polymer blends, such nanofibers can also contain metals, ceramics, etc., often introduced in the form of nanoparticles embedded in the spinning solution. Especially in case of magnetic nanoparticles, the physical properties of the whole nanofiber mats will strongly depend on the dispersion of the nanoparticles in the fibers – while small single nanoparticles may show superparamagnetic behavior, larger agglomerations will rather tend to showing ferromagnetic properties. Investigations of the magnetic properties of a sample with high spatial resolution are mostly performed by magnetic force microscopy (MFM). This technique, however, is usually applied on very flat surfaces of thin-film or nanostructured samples. Here, we report for the first time on MFM measurements on magnetic nanofiber mats, proving in principle that this technique can be used to investigate magnetic nanofiber mats, while the highly uneven nanofiber structure still causes large problems which have to be solved in the future.